Analysis of Memorable Tourism Experience on Behavioral Intention in Alamendah Tourism Village - Kartika, Titing; Edison, Emron (Jurnal Penelitian Pariwisata, 2023)
This study aims to determine the effect of memorable tourist experiences on behavioral intentions in the Alamendah tourism village. This type of research is descriptive and quantitative, collecting data by distributing questionnaires. The research population was all visitors to the Alamendah Tourism Village, with a total sample of 78 respondents using accidental sampling. The results of the study show that memorable travel experiences have a significant effect on behavioral intentions. In this study, a memorable travel experience can positively impact the behavioral intentions of visitors to the Alamendah Tourism Village, including the emotions involved when visitors have a positive experience. These visitors identify with the values ​​or norms that apply in the Alamendah Tourism Village. , Satisfaction of visitors who are satisfied with their travel experience, both the facilities provided services, and the overall tourist experience, environmental influences, visitors who are involved in an environment that supports positive behavior. Therefore, the Alamendah Tourism Village manager needs to provide a satisfying travel experience that encourages the positive behavior of its visitors. Keywords: Tourism Village, Experience, Memorable Tourism Experience, Behaviour Intention